Peran Guru Dalam Implementasi Pembelajaran Project Based Learning di TK Kelinci - Zahra, Nur Amalia; Koimah , Siti Mariyatul (CV. Kurnia Grup, 2024)
This study aims to identify the role of teachers in implementing Project-Based Learning (PBL) at TK Kelinci Kindergarten, focusing on enhancing student engagement through meaningful projects. A qualitative approach with a case study design was used, gathering data through in-depth interviews, direct observations, and documentation. Findings indicate that teachers play a crucial role as facilitators and mentors in PBL, providing the guidance and support necessary for students to complete their projects. Key challenges in implementing PBL include time constraints, limited resources, and parental support. Nevertheless, teachers successfully address these challenges by developing time management strategies and fostering partnerships with the community. The positive impacts of PBL implementation at TK Kelinci include improvements in critical thinking, creativity, collaboration, as well as students’ sense of responsibility and independence.